AES Based Digital Data Security System - Jadhav, R; Redake, SS; Patil, PR; Patil, SV; Jain, KR (International Journal of Computer Sciences and Engineering, 2025)
Financial records, health records, government documents, business documents and quality control information often start out in paper form. While this paper-based records and documents are gradually digitized, security concerns about how such electronic data is stored and transmitted have increased. The prevention of unauthorized modification and loss of records is highly important in the all this sectors. It is hard to keep track of who has used or copied which paper documents. Paper documents are often maintained with very low security control. Therefore, a secured system is not only required but also important. This paper presents system for the management of paper document securely in the digital form. Document digitization refers to the process of capturing the image of a paper document and turning it into digital form. A document scanner is usually used for capturing the document image. While saving the digitized document it is encrypted first and then saved or direct transmitted as per the need. In this paper, we use the AES encryption algorithm to secure data.